The Influence of Past Metronidazole Exposure on the Outcome of Helicobacter pylori Eradication - Choe, Younghee; Kim, Joon Sung; Choi, Hyun Ho; Kim, Dae Bum; Park, Jae Myung; Oh, Jung Hwan; Kim, Tae Ho; Cheung, Dae Young; Chung, Woo Chul; Kim, Byung-Wook; Kim, Sung Soo (Frontiers in Microbiology, 2022)
Background Bismuth quadruple therapy (BQT) is recommended as empirical first-line therapy because it is not affected by antibiotic resistance. We examined whether past exposure to metronidazole affected BQT outcomes. Methods The records of seven hospitals were searched for patients who received BQT for Helicobacter pylori eradication between 2009 and 2020. The association between past metronidazole exposure and the eradication rate was evaluated. Results This study was a multicenter retrospective study. Around 37,602 people tested for H. pylori infection were identified, and 7,233 received BQT. About 2,802 (38.7%) underwent a 13C-urea breath test to confirm eradication. The BQT efficacy was 86.4% among patients without metronidazole exposure and 72.8% among patients with exposure (p < 0.001). The eradication rate of BQT 14 days in patients with past exposure was higher than that of BQT <14 days (85.5 vs. 66.0%, p = 0.009). Multivariate analysis revealed that past metronidazole exposure [odds ratio (OR) 2.6, 95% CI 1.8–3.7; p < 0.001] and BQT <14 days (OR 1.5, 95% CI 1.2–2.0; p = 0.002) were independent risk factors for eradication failure. Conclusion Past metronidazole exposure significantly lowered the BQT eradication rate. BQT 14 days should be recommended for patients with suspected metronidazole exposure.